Exploring the Influence of Alcohol Industry Funding in Observational Studies on Moderate Alcohol Consumption and Health. Issue 5 (11th May 2020) - Vos, Moniek; van Soest, Annick P M; van Wingerden, Tim; Janse, Marion L; Dijk, Rick M; Brouwer, Rutger J; de Koning, Iris; Feskens, Edith J M; Sierksma, Aafje
ABSTRACT: Funding of research by industry in general can lead to sponsorship bias. The aim of the current study was to conduct an initial exploration of the impact of sponsorship bias in observational alcohol research by focusing on a broad spectrum of health outcomes. The purpose was to determine whether the outcome depended on funding source. We focused on moderate alcohol consumption and used meta-analyses that are the basis of several international alcohol guidelines. These meta-analyses included observational studies that investigated the association of alcohol consumption with 14 different health outcomes, including all-cause mortality, several cardiovascular diseases and cancers, dementia, and type 2 diabetes. Subgroup analyses and metaregressions were conducted to investigate the association between moderate alcohol consumption and the risk of different health outcomes, comparing findings of studies funded by the alcohol industry, ones not funded by the alcohol industry, and studies with an unknown funding source. A total of 386 observational studies were included. Twenty-one studies (5.4%) were funded by the alcohol industry, 309 studies (80.1%) were not funded by the alcohol industry, and for the remaining 56 studies (14.5%) the funding source was unknown. Subgroup analyses and metaregressions did not show an effect of funding source on the association between moderate alcohol intake and different health outcomes. In conclusion, only a small proportion of observational studies in meta-analyses, referred to by several international alcohol guidelines, are funded by the alcohol industry. Based on this selection of observational studies the association between moderate alcohol consumption and different health outcomes does not seem to be related to funding source.